Design And Implementation Of The First Trip Signal Detection In A Machinery Assembly System - Zamseleni, Lutfi Mohamed (2007)

(untitled)
This study can give the solutions for many problems. The water pump or boiler in the vapory power station for example, often gets out of service. The main causes for this problem and the reasons behind its repetition can be due to both human and technical factors, i.e., the causes can be from the maintenance operators in the control room, mechanical maintenance, and electrical maintenance and protection systems. Similarly, the malfunction of device may occur as a result of incorrect connection of the wires or the problem of the virtual design of the machine. Therefore, reliable solution to entirely get rid of these problems or the substantial part of them is required. These can be achieved by designing a system to capture these problems, which then be accordingly tackled by finding the virtual and direct solutions. The thesis describes the design and implementation of the first trip signal detection in machinery assembly system. The program used in this study was written specifically to handle above-mentioned problems for this system using the Microsoft Visual Basic 6.0. The system consists of the system circuit-using personal computer, ADAM-4561, ADAM-4068, ADAM-4051,RS-485 networks, power requirements, 16-external input relays and alarm sound. The system catches both 0 and 1 input digital trip signals. Any type of voltage relay DC or AC Voltage is used for external relays and the system can also be used for both digital and analog signals, operating between 5.5V to 10V for the digital signal; and between 5.5V to 10V for the analog signal. It is important to note that the system used in this study has top security secured by the use of a main password in the software system and can’t be using the system without knowing the Executive. Similarly, the system has been designed to be easily carried to any unit by choosing the entire device as small as possible and connecting to the laptop. The system is designed to easily test by including the sixteen external input relays (AC Relays or DC Relays) to test the system. Energize any relays from the sixteen relays or two or three relays together, etc., and users can clearly see on the computer screen the first trip signal data and hear the alarm sound when the first trip signal comes in. Then the system can using to catch sixteen problems in any workplace by using the sixteen channels that in the system. The system includes being accurate between 5.5 V to 10 V for both analog and digital signals directly to the system without relays to catch the first trip signal for this type of signals. To add to this, the system has also been successfully designed and implemented for quick and accurate results. The design, the construction and the testing of the system are presented in this thesis. The system is a simple, fast and accurate method to catch the first trip signal for any machinery assembly system that has sixteen channels and save all the information related to the first trip signal (name, location, office and control room telephone numbers, date, time, etc.). The accuracy of the system was tested and the test has been successful